Evaluation of antibiotics as potential antiproliferative agent against triple-negative breast cancer: a cell-based repurposing study - Khaled Mahmoud; Salwa M El-Hallouty; Ahmed A F. Soliman; Zeinab A Elshahid; Elham M. Youssef (Journal of the Arab Society for Medical Research, 2025)
Background/aim Drug repurposing is a well-known strategy that involves identifying new therapeutic applications for existing medications. Given the global burden of breast cancer, this study aims to investigate the potential of repurposing antibiotics as a potential treatment option for this disease. Patients and methods Cytotoxic activity of about 50 antibiotics against triple-negative breast cancer cell line (MDA-MB231) was investigated using a 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The potency of these antibiotics was compared with doxorubicin as positive control while their specificity was assessed using the noncancerous cell line (BJ-1). A three-dimensional model was also used for determining the penetration power of the strongest antibiotics and an acid phosphatase assay was used to evaluate their cytotoxic effects. Moreover, gene expression analysis of P53, Bcl-2, and Bax was performed using real-time PCR. Results A screening assay was conducted to evaluate the cytotoxic effects of 50 antibiotics against MDA-MB-231 breast cancer cells. At a concentration of 100 μM, 19 antibiotics demonstrated significant cytotoxicity reducing cell viability by more than 50% after 48 h and nonsignificant affecting on normal cells. Additionally, two of these antibiotics coded with S44 and S49, exhibited potent anticancer activity with high penetration power, as evidenced by their ability to shrink three-dimensional spheroids of MDA-MB-231 cells with diameters less than untreated cells. The real-time PCR showed a significant upregulation (P<0.5) in the P53 and Bax levels, while Bcl-2 expression was down regulated significantly (P<0.5) by S44 and S49. Conclusion The findings suggest that repurposing antibiotics may offer promising therapeutic avenues for triple-negative breast cancer treatment. Further investigations are warranted to elucidate the underlying mechanisms of action and evaluate the clinical potential of these compounds.